The Correlation Between Family Support and Knowledge of Sexual Behavior in Adolescents at SMA Negeri 1 Sumpiuh - Yolanda Veldiana; Nur Isnaini (Proceedings Series on Health & Medical Sciences, 2022)
Background: Adolescence is a significant phase in the developmental stage. It starts from the age of 10 to 19 years. Family support and adolescent knowledge about sexual behavior greatly affect adolescent relationships since family or parents are people who are very close to them. Parents play an important role in advising their children about good things. Adolescent knowledge can be obtained at school, in a home environment, or even from parents. The knowledge obtained in the school environment is added to the one obtained at home or in the family. Objective: This study aimed to determine the correlation between family support and knowledge of sexual behavior in adolescents at SMA Negeri 1 Sumpiuh and the characteristics of respondents based on age, gender, and dating status. Methods: This study used a quantitative descriptive study with a cross- sectional design. The amount of the sample was 80 respondents. Results: The result showed that 41 respondents (51.3%) had family support. Then, the p-value of 41 respondents obtained from the chi-square test was 0.000. Conclusion: Adolescents at SMA Negeri 1 Sunpiuh is related to the family support and knowledge of sexual behavior.